2007
DOI: 10.1109/tap.2007.905867
|View full text |Cite
|
Sign up to set email alerts
|

Propagation Mechanisms of Radio Waves Over Intra-Chip Channels With Integrated Antennas: Frequency-Domain Measurements and Time-Domain Analysis

Abstract: Propagation mechanisms of radio waves over intra-chip channels with integrated antennas : frequency-domain measurements and time-domain analysis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 14 publications
(26 reference statements)
0
67
1
1
Order By: Relevance
“…Propagation mechanisms of radio waves over intra-chip channels with integrated antennas were also investigated [3]. Indeed, zig-zag monopole antennas of axial length 1-2 mm can achieve a communication range of about 10-15 mm.…”
Section: B Physical Layer Designmentioning
confidence: 99%
“…Propagation mechanisms of radio waves over intra-chip channels with integrated antennas were also investigated [3]. Indeed, zig-zag monopole antennas of axial length 1-2 mm can achieve a communication range of about 10-15 mm.…”
Section: B Physical Layer Designmentioning
confidence: 99%
“…They have primarily used metal zig-zag antennas operating in the range of tens of GHz. The propagation mechanisms of radio waves over intra-chip channels with integrated antennas were also investigated [50]. It was shown that zig-zag monopole antennas of axial length 1-2 mm can achieve a communication range of about 10-15 mm.…”
Section: Wireless Nocmentioning
confidence: 99%
“…Interconnects in multicore high performance computing architectures are the major drivers of such inconsistent requirements for design with mobile data cloud and intraroom multimedia [2, 4-9]; channel path loss quantification/model becomes necessary for specification of choice of channel bandwidths and any mitigation technique for channel distortion and interference such as equalization (e.g., filter) for adequate systems design. Attempts have been made by different researchers such as [1,[10][11][12][13][14][15][16] to model the propagation pattern in on-chips but less attention on interchip communication [13,17] and the general free space path loss model [18] remains unattended. Since interchip communication is key in system designs, then it becomes necessary to have an estimated path loss for adequate systems design.…”
Section: Introductionmentioning
confidence: 99%